ANALYSIS OF GENETIC CHARACTERISTICS OF INFLUENZA VIRUS A/CHICKEN/CHELYABINSK/30/2019 H9N2 ISOLATED IN CHELYABINSK OBLAST - N. G. Zinyakov; Щю S. Osipova; P. B. Akshalova; V. Yu. Sosipatorova; A. V. Andriyasov; D. B. Andreychuk; I. A. Chvala (Ветеринария сегодня)
The paper presents data on the study of genetic characteristics of the infl uenza virus A/chicken/ Chelyabinsk/30/2019 H9N2 isolated from pathological material (chicken internal organs) in February 2019 and received from the poultry farm in the Chelyabinsk Oblast. The H9N2 subtype of the isolated virus was identifi ed based on virological analysis. Sequencing of the hemagglutinin gene segment revealed that the amino acid sequence at the cleavage site was RSSR/GLF, which is characteristic of a low virulent avian infl uenza virus. Phylogenetic analysis of the obtained nucleotide sequences of the hemagglutinin gene fragment (1–1539 bp open reading frame) showed that the A/chicken/Chelyabinsk/30/2019 H9N2 isolate belongs to the G1 genetic group of the low virulent infl uenza virus A/H9, the representatives of which are widely spread in the Middle Eastern and Central Asian countries. The complete nucleotide genome sequence of the studied pathogen was determined. The comparative analysis of all genomic segments using the GenBank database revealed a close relationship (over 99%) between the A/chicken/Chelyabinsk/30/2019 H9N2 virus and the A/H9 infl uenza virus isolates circulating in Israel in 2006–2012. According to the analysis of the predicted amino acid sequence of the studied isolate, the positions of some molecular markers that determine the biological properties of the virus have been identifi ed. Most amino acid positions of hemagglutinin (according to H3 subtype sequence numbering) suggest affi nity for the ACA2-3Gal-receptors of avian epithelial cells. Amino acid substitutions were detected at the site within the receptor-binding domain as compared to the A/H9N2 infl uenza virus isolates obtained in Russia in 2018. The primary structure of the A/chicken/Chelyabinsk/30/2019 H9N2 isolate demonstrates a very high level of genetic similarity to the infl uenza virus isolate A/chicken/ Israel/215/2007 H9N2 used as a vaccine strain.